The Effect of Computer-Mediated Communication on Occupational Positive Mental Health Mediated by Work-Family Enrichment in Workers in Remote Areas: Analysis using Structural Equation Modelling - Junanta, Herlando; Wibowo, Suryo; ., Herqutanto; Fitriani, Dewi Yunia; Mariyamah, Titis; Soemarko, Dewi Sumaryani (UI Scholars Hub, 2025)
Objective: This study aims to examine the effect of computer-mediated communication (CMC) on occupational positive mental health (OPMH) mediated by work-family enrichment (WFE) in workers in remote areas using the CMC, OPMH-40, and WFE questionnaires. Method: The latent variables in this study are CMC, OPMH, and WFE. The observed variables include all items from CMC, OPMH, and WFE. The sample technique used was total sampling, revealing that 349 workers in the project department of an oil and gas company located in the West Papua Province of Indonesia expressed their willingness to participate as research participants. To test research hypotheses using structural equation modeling (SEM) analysis by testing measurement and structural models. Results: The results showed that the effect of WFE as a mediator strengthened the influence of CMC on OPMH in comparison to the direct effect. Conclusion: This study explains the mechanism by which WFE, acting as a partial mediator, increases the effect of CMC on OPMH. The communication between workers and their families will increase their mental health as it serves as a means of support for workers who are geographically separated from their family. Company management needs to support employees in implementing CMC with their families to increase OPMH and WFE, as well as reduce the negative influence of work-to-family conflict, so that work productivity will increase.